Outpatient Nursing Care (IONC) Model Effect on Self Care Patients with Pain in Outpatient Hospital - Inayah, Iin (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2025)
Background: Supporting self-care and managing pain effectively are critical elements of nursing practice in outpatient settings. Despite their importance, structured care models aimed at enhancing self-care behaviors among patients with pain are still underutilized in many outpatient environments. Objective: This study aimed to assess the effectiveness of the Inayah Outpatient Nursing Care (IONC) Model in improving self-care abilities among patients experiencing pain in a hospital outpatient setting. Methods: A quasi-experimental approach with a non-equivalent control group design was employed. The study was conducted at a public outpatient hospital in Bogor, West Java, Indonesia. A total of 200 patients were selected through purposive sampling, with 100 participants each in the intervention and control groups. Those in the intervention group received nursing care guided by the IONC Model, while the control group received standard outpatient nursing care. The impact on self-care was evaluated using a paired t-test to compare pre- and post-intervention scores. Results: Participants who received care based on the IONC Model showed a statistically significant improvement in self-care abilities for pain management (p = 0.0001). The control group did not exhibit a comparable change (p = 0.172). A significant difference was also observed between the post-test scores of the two groups (p = 0.0001), indicating the model’s effectiveness. Conclusion: The IONC Model demonstrates strong potential for enhancing self-care among outpatients dealing with pain. Incorporating this model into routine nursing practices could lead to improved health outcomes in outpatient care settings.